Determinants of Post-Traumatic Stress Disorders in Italian university students during the Covid-19 outbreak: the leading role of sex, health concerns, and health engagement - Dellafiore, F.; Caruso, R.; Nania, T.; Pittella, E.; Barello, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The unprecedented changes in daily-life caused by Covid-19 restrictions had many psychological and adverse effects, not only in sufferers but also in the general population, including university students. To date, little is known about Post-Traumatic Stress Disorder symptoms experienced by university students during the peak of Covid-19 in Italy. Thus, the study describes Post-Traumatic Stress Disorders related to the Covid-19 outbreak among Italian university students and identifies the psychological distress risk and protective factors. Study design. A multicentre observational cross-sectional study. Methods. Data collection was involved in a self-reported web questionnaire, using the on-line platform Qualtrics®, in March and April 2020, involving convenience and consecutive sampling of Italians university students in different Italy regions. Results. A sample of 720 Italian university students was enrolled. Data analysis highlighted the leading role of sex, health concerns, and health engagement as negative or positive determinants of Post-Traumatic Stress Disorders in Italian university students during the Covid-19 outbreak. In particular, it is very insightful having discovered that health engagement is a protective factor of students’ mental health. Conclusions. This is the first study identifying sex, health issues and health commitment as positive or negative determinants of Post-Traumatic Stress Disorders symptoms in Italian university students during the Covid-19 epidemic. Accordingly, this new achievement could be the starting point for the development of awareness campaigns for the psychological health of Italian university students.